Bagaimana Circle Pertemanan Membentuk Dinamika Sosial Siswa di Sekolah SMK Fajar Ciseeng, Jl. Fajar, RT.007/RW003, Kelurahan Babakan, Kecamatan. Ciseeng, Kabupaten Bogor, Jawa Barat 16120 - Linda Stevani; Balqis Salsabila Putri; Marliana Nur Shabrina; Irfan Rizka Akbar (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
Friendship circles in the school environment often become the first space for students to learn to understand themselves, interact, and build social relationships. In the context of SMK Fajar Ciseeng, friendship circles have unique dynamics influenced by the diverse characteristics, interests, and backgrounds of the students. This Community Service Proposal (Pengabdian kepada Masyarakat/PKM) aims to examine and provide guidance on how friendship circles shape students’ social dynamics at school. The activities are implemented through observations, group discussions, interpersonal skills workshops, and collaborative simulations involving students, teachers, and the school community. Through this series of activities, students are expected to be able to recognize the roles and influences of friendships in the development of their attitudes, communication, and interaction patterns. In addition, this program encourages the creation of healthy, supportive, and inclusive friendship environments as a foundation for fostering a positive school social climate. Therefore, this PKM activity is expected to make a tangible contribution to improving students’ social literacy and strengthening interpersonal relationships at SMK Fajar Ciseeng..